Experiences of developed countries to increase the standard of living of the population - Xodjaniyazov Shohruh Yuldashevich; Zakirova Gulnoza Qudratovna (Genius Publishing Group, 2023)
This article discusses the experiences of developed countries in increasing the standard of living of their populations. The article explores the methods used by these countries, including investments in education and healthcare, social welfare programs, and economic policies that promote growth and innovation. The article concludes by offering suggestions for developing countries to improve their own standards of living
Keywords: developed countries; standard of living; education